Edging along a Warming Coast: A Range Extension for a Common Sandy Beach Crab. - David S Schoeman; Thomas A Schlacher; Alan R Jones; Anna Murray; Chantal M Huijbers; Andrew D Olds; Rod M Connolly (PLoS ONE, 2015)
Determining the position of range edges is the first step in developing an understanding of the ecological and evolutionary dynamics in play as species' ranges shift in response to climate change. Here, we study the leading (poleward) range edge of Ocypode cordimanus, a ghost crab that is common along the central to northern east coast of Australia. Our study establishes the poleward range edge of adults of this species to be at Merimbula (36.90°S, 149.93°E), 270 km (along the coast) south of the previous southernmost museum record. We also establish that dispersal of pelagic larvae results in recruitment to beaches 248 km (along the coast; 0.9° of latitude) beyond the adult range edge we have documented here. Although we cannot conclusively demonstrate that the leading range edge for this species has moved polewards in response to climate change, this range edge does fall within a "hotspot" of ocean warming, where surface isotherms are moving southwards along the coast at 20-50 km.decade-1; coastal air temperatures in the region are also warming. If these patterns persist, future range extensions could be anticipated. On the basis of their ecology, allied with their occupancy of ocean beaches, which are home to taxa that are particularly amenable to climate-change studies, we propose that ghost crabs like O. cordimanus represent ideal model organisms with which to study ecological and evolutionary processes associated with climate change. The fact that "hotspots" of ocean warming on four other continents correspond with poleward range edges of ghost crab species suggests that results of hypothesis tests could be generalized, yielding excellent opportunities to rapidly progress knowledge in this field.